Designing Adaptive Multimodal Literacy in LMS: Empowering Pre-Service Teachers through Asynchronous Learning Innovation - Kusumaningrum, Shirly Rizki; Dewi, Radeni Sukma Indra; Mashfufah, Aynin (Journal of English Language and Education, 2026)
This study explores the development and implementation of an adaptive multimodal literacy module within a Learning Management System (LMS) to enhance literacy instruction in teacher education. Grounded in evidence-based literacy instruction, multimodal literacy theory, and adaptive learning pedagogy, the module was designed following the ADDIE model and implemented among 60 pre-service English teachers enrolled in a literacy course. Using a research and development design, data were collected through literacy pre- and post-tests, engagement questionnaires, LMS analytics, and reflective discussions. Results revealed a statistically significant improvement in literacy competence (t(59) = 9.67, p .001, d = 0.92), with notable gains in reading comprehension, vocabulary acquisition, and multimodal text interpretation. LMS data indicated increased engagement, reflected in a 92% completion rate and high mean engagement score (4.36). Qualitative findings further showed enhanced metacognitive awareness and professional reflection, as participants began to conceptualize literacy teaching through multimodal and adaptive perspectives. Despite these achievements, challenges included technical constraints and initial confusion navigating adaptive branches. Overall, the study demonstrates that adaptive multimodal literacy instruction can effectively integrate cognitive, affective, and reflective dimensions of learning in asynchronous environments. The approach not only promotes literacy mastery but also models digital pedagogy for future teachers. Findings provide valuable insights for higher education institutions seeking to design scalable, learner-centered innovations that connect adaptive technology with transformative literacy practices.